Correlation Between Supervision and Collaboration Using Trello to Enhance Quality of Photobooth Service: Case Study on Kotak Narsis Photobooth - Taufiq, Muhammad; Pono, Maat; Hamid, Nurdjannah (PT. Maju Malaqbi Makkarana, 2023)
The aim of this study is to explore the effectiveness of Trello in improving communication and collaboration enhance quality of service within a service company. The study will use a qualitative approach to collect and analyze data. Qualitative data will be collected through interviews with the CEO and Employee of Kotak Narsis, while the financial report 2020-2023 and the number of problems encountered will be used as secondary sources of data. The qualitative data from the interviews will be analyzed using thematic analysis to identify key themes and patterns in the data. Based on the results of the interviews, it appears that Trello can be an effective solution to the problems faced by the company, mainly poor quality of service. The company also found that the quality of the company's photobooth selfie box service improved, as evidenced by the reduced number of customer complaints.